Development of a Taqman-based real-time PCR assay for detection of porcine sapelovirus infection in pigs. Issue 3 (3rd May 2020) - Kumari, Swati; Ray, P. K.; Singh, Rahul; Desingu, P. A.; Sharma, G. Taru; Saikumar, G.
Abstract: The objective of the present study was to develop a rapid, simple, specific and sensitive Taqman-based real-time PCR assay for porcine sapelovirus (PSV) detection. Specific primers and probe were designed from the five untranslated regions (UTRs) of the viral genome. The detection limit of the real-time PCR was 10 2 copies. The specificity of the Taqman real-time PCR assay was evaluated using other animal viruses and nuclease free water as a negative control. Strong fluorescent signals were obtained only in the detection of PSV real-time PCR and conventional RT-PCR were preformed simultaneously on 90 faecal samples. Based on conventional RT-PCR study 17.7% (16/90) of the faecal samples were positive for PSV. Whereas 21 of 90 samples (23.3%) were positive by real-time RT-PCR. The results showed that real-time PCR was more sensitive than the conventional RT-PCR assay. In conclusion, the Taqman real-time PCR assay for detection of PSV developed, herein, is sensitive, specific, and reliable. This assay will be useful for clinical diagnosis, epidemiological, and pathogenesis studies.